经济相互依赖对两岸政治关, 系走向的影响 ：以ECFA为研究个案 = The implications of economic interdependence on cross-strait political relations : a research based on the case study of ECFA - 郑裕翔 Tay, Yuxiang (2013)
在过去的几十年里，无论是中国还是台湾政府，都试图通过政治渠道来操纵两岸间的经济活动。在这种特殊的政治环境下， 经济决策的理性已遭到扭曲。各个政策的着重点已不再取决于成ᴀ效益分析，而是成为了各政治派系争夺利 益，及在国家身份认同与发展重点的课题上意见分歧，结合形成的写照。这就导致政策在施行方面受到拖延，在制订方面也缺乏协调，更使得各商业团体的经济诉求无法得到及时的处理。2010 年 6 月 29 日台湾与中国签署了具有里程碑与历史性意义的两岸经济合作协议（Economic Cooperation Framework Agreement，以下简称 ECFA）。此协议于 2010 年 9 月 12 日正式生效。台湾国民党政府认为此协议将有利于台湾经济迈向新的阶段。民进党则不以为然，认为 ECFA 不但无利于台湾经济，向大陆企业开放台湾市场反而会给台湾产生种种负面的影响，并指出虽然ECFA 焦点集中在台湾与中国的经贸关系，但无可厚非的 ECFA 仍然会导致两岸在国家安全、战略部署和政治权利上的起伏。最终导致台湾经济过于依赖中国而陷于不利的地位。ECFA 的签署标志着两岸经济关系进入了合作深化，互利共赢，相互依赖的新阶段。ECFA 的签署生效对两岸经贸发展的促进作用得到了两岸专家学者的一致肯定，但是目前学术界对 ECFA 签署后两岸政治关系将如何走向和发展意见分歧。虽然少数学者进行了初步探讨，但研究不深且缺乏理论性和系统性，因此ᴀ文将结合经济学理论与国际关系理论中的相互依赖论，通过构建动态博弈理论模型来探讨 ECFA 签署后两岸政治关系的走向和发展。 The Cross-Strait economic activities for the past few decades were largely dictated by the political agendas of the Mainland and the Taiwanese governments. In such an intriguing and calculating political environment, the soundness of Cross-Strait economic decisions has been seriously compromised. Rather than maximizing profits through investment and trade, political in-fighting within the two governments and bickering over national identities became the major, and often, the sole consideration in the formulation economic policies. Consequently, the development and implementation of many sound economic policies aimed at improving Cross-Strait economic ties have been unnecessarily obstructed. The coordination among the various agencies responsible for policy formulation has often been rendered inefficient. As a result, valid and important economic concerns of various Taiwanese entities that engage in economic activities with the Mainland have often been ignored. Then, on 29 June 2010, the historical Cross-Strait Economic Cooperation Framework Agreement (ECFA) was signed between Taiwan and China. This milestone agreement came into effect on 12 September 2010. While the Kuomintang government claims that ECFA is key to a vibrant economy in the future, the opposition Democratic People’s Party (DPP) argues that the potential costs of the ECFA far outweigh any future benefits. Rather than spurring economic growth, opening the domestic market to Mainland companies would only hurt the local economy and would eventually result in the Taiwanese economy becoming over-dependent on the Mainland economy. The DPP further criticizes that although the apparent aim of the ECFA is to promote Cross-Strait economic exchanges, it is in fact no more than a thinly veiled Trojan horse that would eventually cause uncertainties and damage to the security, strategic and political futures of Taiwan. This thesis aims to discuss the likely trajectory of the Cross-Strait political relations in the post-ECFA era by employing the economic interdependence theory, the international relations theory, and by constructing a dynamic game theory model.